Condition of banks listed on the Warsaw Stock Exchange during the first 3 months of the pandemic in Poland - Zbigniew Korzeb; Paweł Niedziółka (Journal of Banking and Financial Economics (JBFE), 2020)
The aim of the paper is to assess the condition of commercial banks listed on the Warsaw Stock Exchange after the first three months of the COVID-19 pandemic in Poland. The consolidated results for Q1 and Q2 2020 were used focusing on selected evaluation areas such as: capital adequacy, profitability, liquidity, credit portfolio quality as well as operational efficiency. The authors concluded that as a result of the credit crunch and the retention of previously earned profits, almost every medium (except for mBank SA) and every large bank experienced an increase in capital adequacy ratios. Moreover, the profitability of the banking sector eroded in each group of banks, with the rule that ROE is higher in the group of medium and large banks compared to the small ones. With the exception of Idea Bank SA all banks during the pandemic experienced an improvement in liquidity ratios. There was reported an increase in the cost of risk, with the greatest augmentation in small banks. It is maintained that the larger the bank the lower cost of risk. In almost every institution, the risk is mitigated by an increase in the degree of coverage by provisions for impaired receivables. In small banks there was noticed a deterioration in operational efficiency. In medium and large banks, despite a sharp drop in profits and additional costs associated with the pandemic, the process of efficiency improvement was reinforced.
Keywords: G01; G18; G21; 330; COVID-19; commercial banks; WSE